Alternative method to estimate transaction costs: An empirical investigation pre-, during and post- financial crisis - Abdullah, Mimi Hafizah; Li, Steven (2013)
This study offers an alternative method to estimate transaction costs in stock trading via the implied transaction costs by using the Leland option pricing model. The effectiveness of this new approach is tested by using the S&P/ASX 200 index call options data. On the basis of the actual transaction costs estimates on the Australian Securities Exchange (ASX) documented by previous studies and Roll’s model, the empirical results reveal that this new approach can provide a reliable transaction costs estimate on stock trading in the ASX. The accuracy of the implied transaction costs across option moneyness and maturity and the variation of the implied transaction costs during the recent global financial crisis period are investigated.